Pengembangan website velocity berbantuan canva dengan model PBL untuk meningkatkan kemampuan berpikir kritis matematis - Siti Nurhayati; Anik Yuliani; Luvy Sylviana Zanthy (IKIP Siliwangi, 2026)
This study aimed to develop an interactive learning media assisted by the Canva application integrated with the Problem-Based Learning (PBL) model. The Research and Development (R&D) method was employed using the ADDIE development model. The subjects involved in this study were 26 eighth-grade students at a junior high school in the Parongpong area, West Bandung Regency. Data were collected using a mathematical critical thinking skills test, expert validation sheets, and practicality questionnaires. The results indicated that the developed learning media was highly valid, based on assessments by media experts (89,06%), material experts (91,25%), and language experts (94,44%). The product also met the highly practical criteria, achieving 83,85% in the small-group trial and 86,49% in the large-scale testing. Furthermore, the media's effectiveness was demonstrated by an improvement in students' mathematical critical thinking skills, which fell into the high category with an N-gain score of 0,70. Consequently, it can be concluded that the Canva-assisted interactive learning media using the PBL model is valid, practical, and effective in enhancing students' mathematical critical thinking skills.